Genetic variation for glutenin and gliadins aáociated with quality in durum wheat (Triticum turgidum L. áp. turgidum) landraces from Spain - Aguiriano, E.=700 1 Ruiz, M; Fite, R.; Carrillo, J.M.
(En, Es)
Ilus., 33 ref.
Keywords: TRITICUM TURGIDUM; VARIACION GENETICA; GLUTENINAS; PROLAMINAS; CALIDAD; VARIEDADES; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH